Measuring core inflation in the euro area - Claudio Morana (European Central Bank (ECB), 2000)
We propose a measure of core inflation which is derived from a Markov switching ARFIMA model. The Markov switching ARFIMA model generalises the standard ARFIMA model allowing mean reversion to take place with respect to a changing unconditional mean. By imposing a coswitching restriction for nominal money growth and HICP inflation we are able to identify three regimes and establish a linkage between the long-run dynamics of inflation and money growth. The last regime has been found to be coherent with the objective of price stability and can be tentatively named EMU regime. The core inflation model has been contrasted with other models suggested in the literature and found to be superior in terms of forecasting power.
Keywords: C22; E31; E52; 330; Measuring core inflation